(untitled) (Journal of Hama University, 2022)
This research was conducted at labs of the General Commission for Scientific Agricultural Research in Damascus/ Syria and the Biotechnology Lab, Faculty of Agriculture– Damascus University/ Syria, during the season 2018/2019. ISSR technique (Inter Simple Sequence Repeats) was used to determine the genetic relationship among Nineteen genotypes of durum wheat. 20 primers were used, 17 of them gave polymorphism, with a total of 188 alleles and a polymorphic percentage of 95.55 %. The number of bands per primer varied from a minimum of 7 bands for the primer p20 to a maximum of 17 bands for the primer p7 with an average of 11.06 bands per primer, the average of Polymorphic information content (PIC) was 0.3204. Results showed that the genetic distance ranged between 34 - 69%. The lowest distance (34 %) was recorded between lCAMOR and Zagharian2 and between genotypes DW13 and DW14, this low value of the genetic distance indicates a great degree of genetic relationship. The largest distance 69% was recorded between D.45414 and Cham-7, indicating a far genetic relationship between the two genotypes. It was noted that the tree was divided into two main clusters, the witness (Cham 7) was alone in the first cluster, while the second cluster included the other genotypes that were divided into two clusters with varying degrees of genetic kinship. Our results indicate that the ISSR technique can be used to study genetic kinship among durum wheat genotypes.